Influence of 3-((6-R-quinolin-4- yl)thio)propanoic acid derivatives on rhizogenesis of pink rose clones (rosa damascena mill.) - Zavhorodnii, M. P.; Derevianko, N. P.; Shkopynska, T. Ye.; Kornet, M. M.; Brazhko, O. A.; Завгородній, М. П.; Дерев’янко, Н. П.; Шкопінська, Т. Є.; Корнет, М. М.; Бражко, О. А. (My University, 2022)
Today, in microclonal propagation of plants, there is a demand for effective and low-toxic rhizogenesis stimulators of plant explants. The use of such compounds significantly increases the efficiency of microclonal reproduction. The modern direction in the design of effective non-toxic substances is molecular modeling based on known natural and synthetic compounds. An important place as synthons for development is occupied by nitrogen-containing hetero-cycles, in particular quinoline. Results and discussion. Among the derivatives of 3-((6-R-quinolin-4-yl)thio) propanoic acid, the most toxic compounds were those that did not have alkoxy substituents in the 6th position of the quinoline cycle and no methyl radical in the 2nd position. Sodium salts are more toxic than the corresponding acids. This is due to the increase in water solubility of ionized compounds. Derivatives of 3-((6-R-quinolin-4-yl)thio)propanoic acid (sodium salt of 3-((quinolin-4-yl)thio)propanoic acid (QРА-5) showed the greatest toxic effect on the model of the study of progressive sperm motility ) and 3-((quinolin-4-yl)thio)propanoic acid (QРА-1), which would reduce this indicator by 25–30 % compared to intact. The toxicity assessment of the investigated com-pounds made it possible to determine a number of factors and factors of the structure of molecules, which affected the level of toxic action of 3-((6-R-quinolin-4-yl)thio) propanoic acid derivatives and directions for creating non-toxic growth stimulants in this series of 4-thioderivatives of quinoline. Conclusions. The investigated compounds showed a high stimulating effect on rhizogenesis in vitro in explants of pink rose (Rosa damascena Mill.) variety Lada. The selection of leader compounds for further testing of potential stimulators of rhizogenesis for microclonal propagation of ornamental plants was carried out. The obtained results are of high practical importance for obtaining and further introduction of new effective, low-toxic, less expensive substances for plant reproduction, in the conditions of microclonal production. Сучасним напрямком у конструюванні ефективних нетоксичних речовин є молекулярне моделювання на основі відомих природних та синтетичних сполук. Важливе місце як синтони для розробки займають азото-вмісні гетероцикли, зокрема хінолін. Серед похідних 3-((6-R-хінолін-4-іл)тіо) пропанової кислоти найбільш токсичними є сполуки, які не мають в 6-му положенні хінолінового циклу алкоксизамісників та у 2-му положенні – метильного радикалу. Найбільшу токсичну дію на моделі дослідження прогресивної рухливісті сператозоїдів показали похідні 3-((6-R-хіналін-4-іл)тіо)пропіонової кислоти (натрієва сіль 3-((хіналін-4-іл)тіо) пропіонова кислота (QРА-5) та 3-((хіналін-4-іл)тіо) пропіонова кислота (QРА-1), які знижуть цей показник на 25–30 % порівняно з інтактом. Проведена оцінка токсичності досліджуваних сполук, визначений ряд чинників та факторів будови молекул, які впливають на рівень токсичної дії похідних 3-((хіналін-4-іл)тіо) пропіонової кислоти і напрямки створення нетоксичних ростстимуляторів у цьому ряду. Досліджені сполуки вия-вили високу стимулюючу дію щодо різогенезу в умовах in vitro у експлантатів троянди рожевої (Rosa damascena Mill.) сорту Лада. Проведено відбір сполук-лідерів для подальшого тестування потенційних стимуляторів різогенезу для мікроклонального розмноження декоративних рослин.
Вплив похідних 3-((6-R-хінолін-4-іл)тіо)пропанової кислоти на изогенез клонів троянди рожевої (rosa damascena mill.)
Keywords: derivatives of quinoline and propanoic acid; stimulators of rhizogenesis; bioavailability factors; lipophilicity; toxicity; progressive mobility; похідні хіноліну та пропанової кислоти; хемометричні методи; стимулятори різогенезу; фактори біодоступністі; ліпофільнсть; токсичність; прогресивна рухливість; мікроклональне розмноження рослин